Advantages of retrospective ECG-gating in cardio –thoracic imaging with 16-row multislice computed tomography - Cademartiri, F.; Pavone, P. (Acta Biomedica Atenei Parmensis, 2003)
Purpose: to test the added information of a retrospective ECG-gating to the 16-row Multislice Computed Tomography (MSCT) scan of intrathoracic vessels. Materials and methods: ninety-six patients (61 males, aged 59±20 years) underwent MSCT with a 16-row scanner (Sensation 16, Siemens, Germany) for the study of the thoracic vessels. In group 1 (66 patients) a retrospectively ECG-gated protocol was applied; in the control-group 2 (30 patients) a conventional MSCT protocol for thoracic imaging was applied. Images were scored regarding 1) presence or absence of artifacts determined by breath-hold, beam hardening and mis-triggering; 2) visualization (optimal, mild and poor) of great intrathoracic vessels (aorta, pulmonary arteries and veins); 3) visualization (presence or absence) of proximal, mid and distal coronary arteries (left main - LM, left anterior descending - LAD, circumflex - CX, and right coronary artery - RCA). Results: ascending aorta showed motion artifacts in 7 (24%) cases in group 2 and 2 (4%) in group 1. In group 1, proximal LAD, CX, and RCA were assessable in 89%, 91%, and 89%, respectively. Left main coronary artery was assessable in 61 (92%) and 18 (60%) cases for group 1 and 2, respectively. Conclusions: the retrospectively ECG-gated 16-row MSCT provides information regarding ascending aorta and coronary arteries not available in the conventional scan.